Utilizing cylindrical and cubical specimens with edge notch to determine size-independent fracture quantities of rock materials - Ince, R.; Eren, E. (Gruppo Italiano Frattura, 2026)
[Abstract Not Available]
Keywords: Crack Closure Integral (CCI); Double-K model; Single notched cube bend specimen; Straight-notched disk bend specimen; Two-parameter model (TPM)